Method for oxidizing DCB aluminum nitride ceramic chip
Through the combination of ultrasonic washing, activation treatment and muffle furnace oxidation, the problem of high energy consumption and long period of aluminum nitride ceramic sheet surface treatment is solved, and an oxidation process with simple operation, low energy consumption and short period is realized, and a uniform generation is achieved. The dense alumina layer improves the wetting and mechanical properties of the interface.
Patent Information
- Application Number
- CN202411347252.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-31
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing aluminum nitride ceramic sheet surface treatment technology consumes high energy and has a long cycle, and lacks processes that are simple to operate, low energy consumption and short cycles.
Using a combination of ultrasonic washing, activation treatment, drying and muffle furnace oxidation, it is washed by ultrasonic water with ultrasonic power of 600-1200W and frequency of 30-50Hz, copper powder is applied and heated and dried, and three-stage electric heating and division are used. The temperature rise rate and insulation time are controlled to ensure the formation of a uniform alumina layer.
Aluminum nitride ceramic oxidation process with simple operation, low energy consumption and short periods is realized, and a uniform and dense alumina layer is generated, which improves the wetting and mechanical properties of the interface, and avoids damage to the ceramic flakes and uneven oxidation.
Smart Images

Figure CN119219427A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of semiconductor substrate preparation technology, in particular to a DCB aluminum nitride ceramic sheet oxidation method. Background Art
[0002] Aluminum nitride ceramic copper-clad ceramic substrate technology (AlN-DBC) is a technology that directly solders copper foil on the surface of aluminum nitride ceramic. The substrate produced by this technology has both the high thermal conductivity of aluminum nitride ceramics and the high electrical conductivity of copper foil, and is suitable for high-power power electronic modules. The production process is as follows: 1. Clean and surface treat the AlN substrate; 2. Clean and pre-treat the copper foil; 3. Place the treated copper foil on the AlN substrate and put it into a high-temperature diffusion furnace; 4. Soldering: Heat to 1065-1070℃ in a nitrogen atmosphere to directly solder the copper foil on the AlN substrate; 5. Post-processing: Post-process the soldered substrate, such as inspection and cleaning.
[0003] The surface treatment technology of aluminum nitride ceramic sheets for DBC mainly includes high-temperature oxidation, interface coupling agent treatment, etc. Among them, high-temperature oxidation is to heat the aluminum nitride ceramic substrate to a high temperature in an air atmosphere to form a layer of aluminum oxide with uniform structure and firm adhesion on its surface. Although this method is simple, it has high energy consumption and long cycle. Now there is an urgent need for a surface treatment process for aluminum nitride that is simple to operate, low in energy consumption, and short in cycle.
[0004] In order to overcome the defects of the prior art, the present invention provides a DCB aluminum nitride ceramic sheet oxidation method. Summary of the invention
[0005] The object of the present invention is to provide a DCB aluminum nitride ceramic sheet oxidation method to solve the problems in the prior art.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0007] A DCB aluminum nitride ceramic sheet oxidation method comprises the following steps: ultrasonically washing the aluminum nitride ceramic sheet, performing activation treatment after the ultrasonic washing, drying the activated aluminum nitride ceramic sheet, transferring the aluminum nitride ceramic sheet to a muffle furnace for oxidation after drying, and performing ultrasonic washing again after the oxidation to obtain a finished product.
[0008] More optimally, the ultrasonic washing process parameters are: ultrasonic power is 600-1200W, and frequency is 30-50Hz.
[0009] More optimally, the activation treatment process is to first place the aluminum nitride ceramic sheet, then apply copper powder to the surface of the aluminum nitride ceramic sheet, and then heat and dry to end the activation treatment process.
[0010] More optimally, the powder coating process adopts wet powder coating, and the particle size of the powder coating material is 20-40μm.
[0011] More optimally, copper powder is used for powder coating, and the amount of each component of the copper powder is: by mass fraction, the content of Cu is 99.9wt%, the content of O is 0.04wt%, the content of H2O is less than 0.03wt%, the content of acid insoluble matter is less than 0.04wt%, and the balance is Fe; in the process of wet powder coating, auxiliary glue is also required, and the auxiliary glue is composed of 8% alumina, 0.5% cyanoacrylate adhesive and 91.5% water.
[0012] Optimally, the powder coating parameters are: belt speed 4.5-6.6Hz, drying temperature 110-125℃, feed pressure 0.2-0.3MPa, nozzle pressure 0.2-0.3MPa, single powder coating amount 0.4-0.7g / mm 2 , apply powder 1-3 times.
[0013] More optimally, the heating section adopts three-stage electric heating, the temperature range of the first group is 150-200℃, and the temperature range of the second and third groups is 200-250℃.
[0014] More optimally, the drying section adopts three-stage segmented drying, with three independent heating temperature zones, all of which can be independently controlled, and is equipped with a cold air cooling device, and is equipped with exhaust ducts and exhaust outlets.
[0015] More optimally, the drying process parameters are: the spacing between the aluminum nitride ceramic tiles is 1.5-4.0 cm, the drying section temperature is 90-110°C, and the drying time is 200-300s.
[0016] More optimally, the oxidation process parameters are: setting the spacing between aluminum nitride ceramic sheets to 1.0-2.0cm; the oxidation process includes a heating section, a heat preservation section, and a cooling section; the heating section is divided into two sections, the first section is from 25-30°C to 1000°C, the heating slope is 3-10°C / min, and the second section is from 1000°C to 1000-1200°C, the heating slope is 9-15°C / min; the heat preservation time of the heat preservation section is 100min-180min; the cooling section is also divided into two sections, the first section is a natural cooling stage, the end temperature is 300°C, and the second section continues to cool down to 25-30°C.
[0017] Beneficial effects of the present invention:
[0018] The invention prepares an oxidized aluminum nitride ceramic piece by sequentially performing ultrasonic water washing, activation treatment, drying treatment, oxidation treatment, and ultrasonic water washing on the aluminum nitride ceramic piece. The treatment method is simple to operate, has low energy consumption, and a short cycle, and has good application prospects in the field of semiconductor substrate preparation process technology.
[0019] The advantages of the present invention are: 1. The ultrasonic cleaning process provided in the present invention prevents the hydrolysis of the ceramic piece while ensuring that the ceramic piece is sufficiently clean, and avoids the breakage of the ceramic piece and the shedding of the surface oxide layer caused by ultrasound;
[0020] 2. The present invention uses a special powder coating process to reprocess the surface of the ceramic tile, introduce more Cu elements, enhance the surface activity of the ceramic tile, and introduce more oxygen elements in the subsequent oxidation process of the ceramic tile, which is more conducive to the formation of eutectic solution during sintering and greatly improves the wettability of the interface;
[0021] 3. By setting different temperature zones, it is ensured that the ceramic tile will not crack or break due to temperature differences at high temperatures. The appropriate heating rate is also helpful to form a uniform and dense aluminum oxide layer on the surface of aluminum nitride, and the composition and microstructure of the aluminum oxide layer are basically the same as those of aluminum oxide ceramics. In addition, by setting appropriate spacing, it can be ensured that every position of the ceramic tile is fully oxidized, and uneven oxidation will not occur due to space problems. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:
[0023] Figure 1 1 is the surface microstructure of aluminum oxide and aluminum nitride of the present invention; wherein 1 corresponds to aluminum oxide ceramic, 2 corresponds to the aluminum nitride ceramic sheet prepared in Example 1, 3 corresponds to the aluminum nitride ceramic sheet prepared in Example 2, and 4 corresponds to the aluminum nitride ceramic sheet prepared in Example 3; Figure 2 and Figure 3 Same number as here;
[0024] Figure 2 is the flexural strength value of the aluminum nitride ceramic sheet before and after the oxidation method of the present invention;
[0025] Figure 3 These are ultrasonic scanning images of different aluminum nitrides after sintering according to the present invention. DETAILED DESCRIPTION
[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Source of raw materials:
[0028] Aluminum nitride ceramics, provided by MARUWA, have a composition of 97% AlN and 3% Y2O3.
[0029] Example 1: After the aluminum nitride ceramic pieces were cleaned with 600W, 30Hz ultrasonic waves, copper powder and a powder coating machine were used to activate the surface of the product, and then the spacing between the aluminum nitride ceramic pieces was set to 1.5cm. After drying in a drying tank at 90°C for 200s, the pieces were taken out and placed in a muffle furnace for oxidation process. The spacing between the aluminum nitride ceramic pieces was set to 1.0cm, and the temperature was increased to 1000°C at a heating rate of 3°C / min. After keeping the temperature for 100min, the finished product was obtained after cleaning;
[0030] The activation treatment process is to first place an aluminum nitride ceramic sheet, then apply copper powder to the surface of the aluminum nitride ceramic sheet, and then heat and dry to end the activation treatment process; the powder application stage adopts wet powder application, and the particle size of the powder application material is 35μm; the copper powder meets the following conditions: in terms of mass fraction, the Cu content is 99.9wt%, the O content is 0.04wt%, the H2O content is 0.02wt%, the acid insoluble content is 0.03wt%, and the Fe content is 0.01wt%; the powder application parameters are: the belt speed is 4.5Hz, the drying temperature is 110℃, the feed pressure is 0.2MPa, the nozzle pressure is 0.2MPa, and the single powder application amount is 0.4g / mm 2 , 3 times of powder application: 1.2g / mm 2 The heating section adopts three-stage electric heating, the first group temperature is 200℃, the second and third groups temperature are 250℃; the drying section adopts three-stage segmented drying, three independent heating temperature zones, all of which can be independently controlled, and are equipped with cold air cooling devices, exhaust ducts and exhaust ports; auxiliary glue is also required in the process of wet powder application, which is composed of 8% alumina, 0.5% cyanoacrylate adhesive and 91.5% water.
[0031] Example 2: After the aluminum nitride ceramic pieces were cleaned with 800W, 40Hz ultrasonic waves, copper powder and a powder coating machine were used to activate the surface of the product, and then the spacing between the ceramic pieces was set to 2.5cm. After drying in a drying tank at 100°C for 250s, the pieces were taken out and placed in a muffle furnace for oxidation process. The spacing between the aluminum nitride ceramic pieces was set to 1.5cm, and the temperature was raised to 1000°C at a heating rate of 6°C / min. The second stage of heating was raised to 1100°C at 9°C / min. After keeping warm for 150min, the finished product was obtained after washing.
[0032] The activation treatment process is to first place an aluminum nitride ceramic sheet, then apply copper powder to the surface of the aluminum nitride ceramic sheet, and then heat and dry to end the activation treatment process; the powder application stage adopts wet powder application, and the particle size of the powder application material is 35μm; the copper powder meets the following conditions: in terms of mass fraction, the Cu content is 99.9wt%, the O content is 0.04wt%, the H2O content is 0.02wt%, the acid insoluble content is 0.03wt%, and the Fe content is 0.01wt%; the powder application parameters are: the belt speed is 4.5Hz, the drying temperature is 110℃, the feed pressure is 0.2MPa, the nozzle pressure is 0.2MPa, and the single powder application amount is 0.4g / mm 2 , 3 times of powder application: 1.2g / mm 2 The heating section adopts three-stage electric heating, the first group temperature is 200℃, the second and third groups temperature are 250℃; the drying section adopts three-stage segmented drying, three independent heating temperature zones, all of which can be independently controlled, and are equipped with cold air cooling devices, exhaust ducts and exhaust ports; auxiliary glue is also required in the process of wet powder application, which is composed of 8% alumina, 0.5% cyanoacrylate adhesive and 91.5% water.
[0033] Example 3: After the aluminum nitride ceramic pieces were cleaned with 1200W, 50Hz ultrasonic waves, copper powder and a powder coating machine were used to activate the surface of the product, and then the spacing between the ceramic pieces was set to 4.0cm. After drying in a drying tank at 110°C for 300s, the pieces were taken out and placed in a muffle furnace for oxidation process. The spacing between the aluminum nitride ceramic pieces was set to 2cm, and the temperature was increased to 1000°C at a heating rate of 10°C / min, and the second stage was heated at 15°C / min to 1200°C; after keeping the temperature for 200min, the finished product was obtained after washing;
[0034] The activation treatment process is to first place an aluminum nitride ceramic sheet, then apply copper powder to the surface of the aluminum nitride ceramic sheet, and then heat and dry to end the activation treatment process; the powder application stage adopts wet powder application, and the particle size of the powder application material is 35μm; the copper powder meets the following conditions: in terms of mass fraction, the Cu content is 99.9wt%, the O content is 0.04wt%, the H2O content is 0.02wt%, the acid insoluble content is 0.03wt%, and the Fe content is 0.01wt%; the powder application parameters are: the belt speed is 4.5Hz, the drying temperature is 110℃, the feed pressure is 0.2MPa, the nozzle pressure is 0.2MPa, and the single powder application amount is 0.4g / mm 2 , 3 times of powder application: 1.2g / mm 2The heating section adopts three-stage electric heating, the first group temperature is 200℃, the second and third groups temperature are 250℃; the drying section adopts three-stage segmented drying, three independent heating temperature zones, all of which can be independently controlled, and are equipped with cold air cooling devices, exhaust ducts and exhaust ports; auxiliary glue is also required in the process of wet powder application, which is composed of 8% alumina, 0.5% cyanoacrylate adhesive and 91.5% water.
[0035] Detection test:
[0036] Bending strength test: Test the bending strength in accordance with Chapter 7 of the national standard GB / T 6569-2006.
[0037] Table 1 Surface composition analysis of aluminum oxide and aluminum nitride
[0038]
[0039] Conclusion: As shown in Table 1 above, No. 1 corresponds to alumina ceramics, No. 2 corresponds to the aluminum nitride ceramic sheet prepared in Example 1, No. 3 corresponds to the aluminum nitride ceramic sheet prepared in Example 2, and No. 4 corresponds to the aluminum nitride ceramic sheet prepared in Example 3;
[0040] As attached Figure 1 As shown in the figure, the surface microstructures of Examples 1, 2, and 3 are the same as those of the alumina ceramics, with no obvious difference; as shown in Table 1, the surface composition of Examples 1, 2, and 3 is the same as that of the alumina ceramics, with no obvious difference; this result shows that the present invention generates a uniform and dense alumina layer on the surface of aluminum nitride ceramics, which can achieve an effect similar to that of the surface of the alumina ceramics.
[0041] As attached Figure 2 As described above, the aluminum nitride ceramic sheets treated in Examples 1, 2, and 3 have the same bending strength as the original aluminum nitride ceramic sheets; this result indicates that the oxidation treatment of the present invention does not reduce the mechanical properties of the aluminum nitride ceramic sheets.
[0042] As attached Figure 3 As shown, the aluminum nitride ceramic sheets prepared in Examples 1, 2, and 3 have the same ultrasonic scanning state after sintering, without obvious dispersed bubbles.
[0043] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.
[0044] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A DCB aluminum nitride ceramic sheet oxidation method, characterized in that: The following steps are involved: The aluminum nitride ceramic sheet is ultrasonically washed, activated after the ultrasonic washing, and then dried. After drying, the aluminum nitride ceramic sheet is transferred to a muffle furnace for oxidation. After the oxidation, the aluminum nitride ceramic sheet is ultrasonically washed again to obtain a finished product.
2. A DCB aluminum nitride ceramic sheet oxidation method according to claim 1, characterized in that: Ultrasonic washing process parameters: ultrasonic power is 600-1200W, frequency is 30-50Hz.
3. A DCB aluminum nitride ceramic sheet oxidation method according to claim 1, characterized in that: The activation treatment process is to first place the aluminum nitride ceramic sheet, then apply copper powder to the surface of the aluminum nitride ceramic sheet, and then heat and dry to end the activation treatment process.
4. A DCB aluminum nitride ceramic sheet oxidation method according to claim 3, characterized in that: The powder coating process adopts wet powder coating, and the particle size of the powder coating material is 20-40μm.
5. A DCB aluminum nitride ceramic sheet oxidation method according to claim 3, characterized in that: Copper powder is used for powder coating, and the amount of each component of the copper powder is as follows: by mass fraction, the content of Cu is 99.9wt%, the content of O is 0.04wt%, the content of H2O is less than 0.03wt%, the content of acid insoluble matter is less than 0.04wt%, and the balance is Fe; in the process of wet powder coating, auxiliary glue is also required, and the auxiliary glue is composed of 8% aluminum oxide, 0.5% cyanoacrylate adhesive and 91.5% water.
6. A DCB aluminum nitride ceramic sheet oxidation method according to claim 3, characterized in that: Powder coating parameters: belt speed is 4.5-6.6Hz, drying temperature is 110-125℃, copper powder feed pressure is 0.2-0.3MPa, nozzle pressure is 0.2-0.3MPa, single powder coating amount is 0.4-0.7g / mm 2 , apply powder 1-3 times.
7. A DCB aluminum nitride ceramic sheet oxidation method according to claim 3, characterized in that: The heating section adopts three-stage electric heating, the temperature range of the first group is 150-200℃, and the temperature range of the second and third groups is 200-250℃.
8. A DCB aluminum nitride ceramic sheet oxidation method according to claim 1, characterized in that: Drying process parameters: the spacing between aluminum nitride tiles is 1.5-4.0 cm, the drying section temperature is 90-110°C, and the drying time is 200-300s.
9. A DCB aluminum nitride ceramic sheet oxidation method according to claim 1, characterized in that: Oxidation process parameters: Set the spacing between aluminum nitride ceramic sheets to 1.0-2.0cm; the oxidation process includes a heating section, a heat preservation section, and a cooling section; the heating section is divided into two sections, the first section is from 25-30°C to 1000°C, the heating slope is 3-10°C / min, and the second section is from 1000°C to 1000-1200°C, the heating slope is 9-15°C / min; the heat preservation time of the heat preservation section is 100min-180min; the cooling section is also divided into two sections, the first section is a natural cooling stage, the end temperature is 300°C, and the second section continues to cool down to 25-30°C.
Citation Information
Patent Citations
Preparation method for copper / aluminium nitride ceramic composite heat-conductive substrate
CN104064478A
Manufacturing method of high-heat-conductivity copper-clad ceramic substrate
CN104362099A
Process for producing a ceramic substrate and a ceramic substrate
US6066219A
